Lonicerin targets EZH2 to alleviate ulcerative colitis by autophagy-mediated NLRP3 inflammasome inactivation - Qi Lv; Yao Xing; Jian Liu; Dong Dong; Yue Liu; Hongzhi Qiao; Yinan Zhang; Lihong Hu (Elsevier, 2021)
Aberrant activation of NLRP3 inflammasome in colonic macrophages strongly associates with the occurrence and progression of ulcerative colitis. Although targeting NLRP3 inflammasome has been considered to be a potential therapy, the underlying mechanism through which pathway the intestinal inflammation is modulated remains controversial. By focusing on the flavonoid lonicerin, one of the most abundant constituents existed in a long historical anti-inflammatory and anti-infectious herb Lonicera japonica Thunb., here we report its therapeutic effect on intestinal inflammation by binding directly to enhancer of zeste homolog 2 (EZH2) histone methyltransferase. EZH2-mediated modification of H3K27me3 promotes the expression of autophagy-related protein 5, which in turn leads to enhanced autophagy and accelerates autolysosome-mediated NLRP3 degradation. Mutations of EZH2 residues (His129 and Arg685) indicated by the dynamic simulation study have found to greatly diminish the protective effect of lonicerin. More importantly, in vivo studies verify that lonicerin dose-dependently disrupts the NLRP3-ASC-pro-caspase-1 complex assembly and alleviates colitis, which is compromised by administration of EZH2 overexpression plasmid. Thus, these findings together put forth the stage for further considering lonicerin as an anti-inflammatory epigenetic agent and suggesting EZH2/ATG5/NLRP3 axis may serve as a novel strategy to prevent ulcerative colitis as well as other inflammatory diseases.